Analytical Framework for Dynamic Capabilities in a Public Organization - Quiñones Huayna, Nilton Marcelo (Revista del CLAD Reforma y Democracia, 2023)
Humanity is going through a change of era and Industry 4.0 is part of that new order. Many Latin American countries are still in the recovery process from the COVID-19 pandemic, a situation that is aggravated by conflicts such as that between Russia and Ukraine and the increasingly serious effects of climate change. These scenarios have emphasized the need for public and private organizations with strategic capabilities to face the challenges of an uncertain and dynamic environment. In the field of Management Sciences, there are several investigations that help to understand why public management fails to perform well in the face of a dynamic, turbulent and uncertain environment. One framework of analysis is that of operational capabilities, which focuses on the analysis of the organization's internal resources (Ongaro & Ferlie, 2020). However, there are other lenses that analyze organizations in changing and uncertain environments, such as dynamic capabilities, which has significant academic development for private sector organizations, but less for public organizations. This article aims to contribute with an analytical framework, based on a literature review, to advance empirical research on public organizations in Latin America. The purpose is to understand the relationships between dynamic capabilities, the ability to detect, exploit and reconfigure, and performance. Also, how exogenous conditions, such as the level of publicity and environmental turbulence, affect them. This information is valuable for public decision makers as it will allow them to understand the capabilities that public organizations need to develop to improve their performance in a changing and uncertain environment.
Keywords: Public Management; Dynamic Capabilities; Public Organizations